Organic meat production and processing - Ricke, Steven C., 1957- (Hoboken, NJ : John Wiley and Sons, 2012)
Organic Meat Production and Processing describes the challenges of production, processing and food safety of organic meat. The editors and international collection of authors explore the trends in organic meats and how the meat industry is impacted. Commencing with chapters on the economics, market and regulatory aspects of organic meats, coverage then extends to management issues for organically raised and processed meat animals. Processing, sensory and human health aspects are covered in detail, as are the incidences of foodborne pathogens in organic beef, swine, poultry and other organic me.
9.4 Current regulations regarding the pet-food industry.
Includes bibliographical references and index.
Keywords: Meat industry and trade; Meat industry and trade -- United States; Natural foods industry; Meat hygiene; Natural foods; Processed foods; Animal industry; Packing-houses.; Animal biotechnology; Engineering; Chemical engineering; TECHNOLOGY & ENGINEERING -- Food Science; Animal biotechnology; Animal industry; Meat hygiene; Meat industry and trade; Natural foods; Natural foods industry; Packing-houses.; Processed foods; United States; Electronic books